Combination Therapy by Tissue-Specific Suicide Gene and Bevacizumab in Intramedullary Spinal Cord Tumor - Gwak, So-Jung (Yonsei Med J, 2020)
PURPOSE: Malignant gliomas are aggressive spinal cord tumors. In this study, we hypothesized that combination therapy using an anti-angiogenic agent, bevacizumab, and hypoxia-inducible glioblastoma-specific suicide gene could reduce tumor growth. MATERIALS AND METHODS: In the present study, we evaluated the effect of combination therapy using bevacizumab and pEpo-NI2-SV-TK in reducing the proliferation of C6 cells and tumor growth in the spinal cord. Spinal cord tumor was generated by the injection of C6 cells into the T5 level of the spinal cord. Complexes of branched polyethylenimine (bPEI)/pEpo-NI2-SV-TK were injected into the spinal cord tumor. Bevacizumab was then administered by an intraperitoneal injection at a dose of 7 mg/kg. The anti-cancer effects of combination therapy were analyzed by histological analyses and magnetic resonance imaging (MRI). The Basso, Beattie and Bresnahan scale scores for all of the treatment groups were recorded every other day for 15 days to assess the rat hind-limb strength. RESULTS: The complexes of bPEI/pEpo-NI2-SV-TK inhibited the viability of C6 cells in the hypoxia condition at 5 days after treatment with ganciclovir. Bevacizumab was decreased in the cell viability of human umbilical vein endothelial cells. Combination therapy reduced the tumor size by histological analyses and MRI. The combination therapy group showed improved hind-limb function compared to the other groups that were administered pEpo-NI2-SV-TK alone or bevacizumab alone. CONCLUSION: This study suggests that combination therapy using bevacizumab with the pEpo-NI2-SV-TK therapeutic gene could be useful for increasing its therapeutic benefits for intramedullary spinal cord tumors.